Investigation of dispersion and nonlinear characteristics of liquid core optical fiber filled with olive oil - Al-Dergazly, Anwaar A. (Sustainable Engineering and Innovation, 2020)
This paper introduces a prospective material for photonic laser applications. Different high purity samples of olive oil were subjected to a spectrophotometer to determine the absorption spectra. The transmission behavior of olive oil is about (44.28) % at a wavelength of 532 nm, while it is (62.94) % at 1064 nm. Then, the nonlinear optical properties represented by the nonlinear refractive index and nonlinear absorption coefficient are determined using a highly sensitive method known as the Z-scan technique. Z-Scan experiment was performed using 1064 nm CW Nd:YAG and 532 nm SHG Nd:YVO4 lasers. n2 = 3.99×10-6W/cm2 and beta = -0.0017 m/W for 1064nm wavelength and n2 = 2.45×10-7W/cm2 and beta =-7.26×10-4 m/W for 532nm wavelength. This paper gives simulation results for a liquid-core optical fiber (LCOF) filled with olive oil. The nonlinear propagation constant and group velocity dispersion (GVD) properties are estimated. The simulation of the generation of LCOF is also obtained. The calculations show that LOCF can provide huge nonlinear parameters and a large span of slow varying GVD characteristics in the visible and infrared region, which have potential applications in optical communications and nonlinear optics. The material is olive oil which is classified as an organic compound, having good nonlinear optical properties making it a potential candidate to be for photonic applications.